Teachers' Creativity in Designing Online Learning Activities to Foster Literacy - Vina Fathira; Mukhaiyar Mukhaiyar; Atmazaki Atmazaki (ELT-Lectura, 2023)
Today’s literacy requirements call for adept readers to be able to do more than just “read between the lines”. Creativity is very important since the changing era and development technology in online learning. The aim of research is teacher’s creativity in designing online learning activities to foster literacy for students in higher education level. The method of this research was descriptive qualitative research. In data collection techniques, researchers used online questionnaire techniques to obtain information. The questionnaire in this study was organized into 10 open-ended statements, compiled in a Google form to make it easier for researchers to obtain research data. In the data analysis technique, the researcher continued the analysis by looking at the answers to the questions that were distributed to the Google form. The result of this research showed that most of the lecturers understand the concept of “creativity” quite well. The findings of this result showed that several lecturers respond this question about the notion of “creativity” based on their own experiences and elaborate some teaching techniques, various media, and some gadget application to refresh students’ interest on the subject. The conclusion of this research was the way of teacher’s creativity in online learning activities to foster literacy for students like firstly know about the notion of creative to foster students’ literacy given by the respondent as a teacher, the way of creating creativity in online learning activities to foster literacy for students.